2021
DOI: 10.3389/fphy.2020.629620
|View full text |Cite
|
Sign up to set email alerts
|

Differential Entropy Feature Signal Extraction Based on Activation Mode and Its Recognition in Convolutional Gated Recurrent Unit Network

Abstract: In brain-computer-interface (BCI) devices, signal acquisition via reducing the electrode channels can reduce the computational complexity of models and filter out the irrelevant noise. Differential entropy (DE) plays an important role in emotional components of signals, which can reflect the area activity differences. Therefore, to extract distinctive feature signals and improve the recognition accuracy based on feature signals, a method of DE feature signal recognition based on a Convolutional Gated Recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The research of Garcia-Martinez et al confirmed the effectiveness and robustness of the DE feature in EEG emotion recognition tasks [21]. Zhu and Zhong [22] classified DE features by using the 2DCNN-BiGRU network and achieved 87.89% and 88.69%, respectively, in the arousal and valence classification results of the DEAP dataset. However, a single convolution scale makes this method limited in spatial feature extraction, resulting in feature loss.…”
Section: Introductionmentioning
confidence: 87%
“…The research of Garcia-Martinez et al confirmed the effectiveness and robustness of the DE feature in EEG emotion recognition tasks [21]. Zhu and Zhong [22] classified DE features by using the 2DCNN-BiGRU network and achieved 87.89% and 88.69%, respectively, in the arousal and valence classification results of the DEAP dataset. However, a single convolution scale makes this method limited in spatial feature extraction, resulting in feature loss.…”
Section: Introductionmentioning
confidence: 87%
“…In this article, we adopt Differential Entropy (DE) (Lan et al, 2019) and Power Spectral Density (PSD) (Fang et al, 2021;Zhu and Zhong, 2021) features for emotion classification. These features have been extensively used in EEG-Based emotion recognition Arnau-Gonzalez et al, 2021;Zhu and Zhong, 2021).…”
Section: Feature Extractionmentioning
confidence: 99%
“…In this article, we adopt Differential Entropy (DE) (Lan et al, 2019) and Power Spectral Density (PSD) (Fang et al, 2021;Zhu and Zhong, 2021) features for emotion classification. These features have been extensively used in EEG-Based emotion recognition Arnau-Gonzalez et al, 2021;Zhu and Zhong, 2021). The feature includes DE and PSD from theta (4 Hz < f <8 Hz), slow alpha (8 Hz < f <10 Hz), alpha (8 Hz < f <12 Hz), beta (12 Hz < f < 30 Hz), and gamma (30 Hz < f ) bands of EEG signal.…”
Section: Feature Extractionmentioning
confidence: 99%
“…In the field of EEG-based emotion recognition, interpolation algorithms are still relatively scarce. Cho et al [51] used RBF interpolation algorithm to construct a new 2D EEG signal frame, which combine with DE characteristics to achieve a higher accuracy. However, RBF is a global interpolation algorithm, which may result in large errors when EEG value is in local drastic variation.…”
Section: Eeg Interpolation Algorithmsmentioning
confidence: 99%